321 Surgery Induction Guidebook – an Aid to a Successful Transition. (28th February 2022) - Abbas, M.K.; Gurung, G.; Lim, E.; Umar, R.; Sharmadaal, A.; Zehra, S.
Abstract: Aim: There is a 4–12% increase in mortality following the August change over in the National Health Service (NHS) UK. A well-structured induction programme is mandatory to improve both the competency and confidence of new junior doctors. This activity was designed to evaluate and improve the induction process in Pilgrim Hospital by introducing an induction guidebook. It aimed to provide a sustainable and reliable source of information to junior doctors. Method: An initial survey in the department assessed the needs and identified the information required for the guidebook. An induction guidebook was designed and circulated during the changeover. A feedback survey was conducted after the six months of the initial Induction guidebook release, to know the usefulness of components of the induction guidebook and identify any gaps to improve the guidebook. Results: A total of 15 participants completed the feedback survey. 47% (7) found the induction guidebook beneficial and 53.3 % (8) found it 'slightly beneficial'. Similarly, only 1 participant (6.7%) rated the guidebook to be "of minor importance", while 53% (8) rating it "very important" part of induction. The feedback for the contents of the book was also encouraging with suggestions. Conclusions: The guidebook proved to be a valuable source in helping new doctors during times of transition to adjust to the local system and improve the induction process. It provided information about local guidelines, job overview, team structure, IT, useful contacts, and other relevant information. We recommend the departmental guidebook as a vital part of local departmental induction during the changeover.